Personality and psychological factors: Effects on dental beliefs - Siddhi Hathiwala; S Acharya; S Patil (Wolters Kluwer Medknow Publications, 2015)
Background: Dental treatment can be highly unpleasant for anxious patients. Despite all advancements, dental anxiety continues to upset the dentist-patient relationship. The psychological factors like individual personality and familial and peer influence may alter the dental beliefs of a patient. Aim: A cross-sectional questionnaire study was conducted among young adolescents to investigate the relationship among various psychological factors and the dental beliefs of an individual. Materials and Methods: A self-administered questionnaire was distributed among higher secondary school children, aged 15−17 years in Udupi district. The dental anxiety of the participants was measured using Modified Dental Beliefs scale and the personality traits were assessed using the Ten-Item Personality Inventory. Pearson's correlation and chi-square analysis were performed among these scales. Independent t-test was performed to compare dental anxiety scores with different socio-demographic and psychological characteristics. Results: In all 198 students, with a mean age of 16.6 years, completed the questionnaire. A majority of the participants had lower MDBS scores. The personality traits like Emotional Stability and Openness to New Experiences showed a negative correlation with the Dental Belief scores. Apart from these, the experience at first dental visit and peer support also affected the dental beliefs of the adolescents. Conclusion: Various psychological traits of adolescents influence their dental anxiety.